Tribology of particle suspensions in rolling-sliding soft contacts. (September 2015) - Yakubov, G.E.; Branfield, T.E.; Bongaerts, J.H.H.; Stokes, J.R.
Abstract: We investigate the lubrication of microsphere suspensions between compliant substrates, and probe the influence of matrix viscosity, particle phase volume, surface roughness and wetting, and slide-to-roll ratio (SRR). In general, the suspensions behave as a continuum in the elastohydrodynamic regime provided the film thickness, which is predicted from the product of speed and viscosity, is greater than the particle diameter. Below this, the frictional response is characteristic of the mixed and boundary regimes. In the boundary regime, friction is independent of phase volume above 5% and it is governed by the rolling friction associated with particles being entrained into the contact that is independent of SRR, which is made possible by substrate deformation. This study provides a benchmark for soft-tribology and biotribology studies involving more complex particle suspensions and particle-containing soft materials. Highlights: The lubrication behaviour of non-interacting microsphere suspensions between compliant substrates has been investigated. Boundary, mixed and elasto-hydrodynamic lubrication regimes have been tested. The influence of matrix viscosity, particle phase volume, surface roughness, wetting, slide-to-roll ratio has been assessed. The boundary regime is dominated by the rolling friction mediated by particles entrained into the compliant contacts. For hydrophobic surfaces, very low amounts of spheres are required to alter the boundary lubrication of the matrix phase.